SCHEDULING WORK UNDER INTEGRATED URBAN DEVELOPMENT USING THE METHOD OF UNCERTAIN RESOURCE COEFFICIENTS - Bolotin, Sergey; Bohan, Haitham; Dadar, Aldyn-kys; Biche-ool, Khenzig (Architecture and Engineering, 2021)
Introduction: Planning integrated development of a residential area involves determining the composition of the objects to be built and creating an appropriate integration mechanism, backed up by a generalized work schedule. The existing methods of forming integrated work schedules do not use a systemic approach, based on a universal mathematical model, to describe the organizational and technological aspects of construction. Methods: The present study uses the method of uncertain resource coefficients to demonstrate a mechanism for systemically describing organizational and technological construction processes. We present a way of adapting this method to forming a generalized construction schedule during integrated development. The proposed adaptation mechanism is based on managing schedule calculations by rationally influencing the elements of the linear equation system that describes the organizational and technological processes. Results and Discussion: The solutions presented in the paper are fully consistent with the calculations obtained by different flow methods of organizing construction, as well as with the critical path method used in project management programs. The method described in the paper has been implemented in well-known project management software, Microsoft Project, as a macro program in the Visual Basic for Applications programming language, making it possible to form, calculate, and optimize a schedule for integrated territory development using the unified software toolkit.